Room-Temperature Transient Absorption in KDP Crystal Under Exposure to Nanosecond Laser at 355 nm - F. Geng; Q. Xu; F. R. Wang; H. D. Xia; J. B. Wen; J. Huang; X. D. Jiang (IEEE Photonics Journal)
Defects in high-purity optical materials produced by high-power laser irradiation have attracted much attention, which could modify material properties and cause degradation or even laser damage of optical components. In this letter, we investigate room-temperature transient absorption properties in visible region of KDP crystals irradiated by a nanosecond ultraviolet (UV) laser at 355 nm. Both the transient absorption spectra and the absorption decay properties are presented and discussed. Transient absorption spectrum of KDP under UV laser irradiation shows a broad absorption band with maximum at about 560 nm. The observed transient absorption band in the KDP crystal is suggested to arise from laser-induced electronic defects identified as hole centers. The decay dynamics of hole center absorption is described by a model of electron tunneling recombination assisted by thermal diffusion. Generation of such defects under UV laser irradiation is considered to have a relationship with initial defects existed in the KDP crystal lattice. A defect-mediated nonlinear absorption model was proposed to explain the hole center generation processes under UV laser irradiation.